Academic self-concept and academic motivation in young talent from the department of Puno - Cahuana Cuti, Mónica (2020)
The objective of the study was to determine the relationship between the variables academic self-concept and academic motivation in young talented people from Puno. The methodology corresponds to the correlational type study, of non-experimental design and cross section; We worked with a population of 80 university beneficiaries of the scholarship program 18 from a private university in Puno, being 48.8% maleand 51.3% female, to whom two documentary measurement instruments were applied: the self-concept sub-scale. AF5 academic and an academic motivation scale, both valid and reliable. The data were processed with the statistical package SPSS (Statistical Package for the Social Sciences) version 22.0 at a significance level of 5% and a confidence level of 95%. The results according to Spearman's Rho correlation coefficient evidenced the existence of a moderate, direct and significant correlation between the research variables (Rho = .497; p = .000) as well as in the intrinsic motivation dimensions (Rho = .475, p = .000) and extrinsic motivation (Rho = .485, p = .000), whereas in Amotivación a low and negative but not significant correlation was found (Rho = -.196, p = .082). It is concluded that the greater the academic self-concept, the greater the academic motivation.